The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/nar/gky335
|View full text |Cite
|
Sign up to set email alerts
|

Translational control plays an important role in the adaptive heat-shock response of Streptomyces coelicolor

Abstract: Stress-induced adaptations require multiple levels of regulation in all organisms to repair cellular damage. In the present study we evaluated the genome-wide transcriptional and translational changes following heat stress exposure in the soil-dwelling model actinomycete bacterium, Streptomyces coelicolor. The combined analysis revealed an unprecedented level of translational control of gene expression, deduced through polysome profiling, in addition to transcriptional changes. Our data show little correlation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
(51 reference statements)
3
9
0
Order By: Relevance
“…These findings demonstrate that transcription of genes for secondary metabolism might be inconsequential to the production of secondary metabolites themselves. Altogether our results caution against overt reliance on transcriptome and translatome data as a proxy to phenotypic expression of actinobacterial BGCs 13,62,63 .…”
Section: Discussionmentioning
confidence: 60%
“…These findings demonstrate that transcription of genes for secondary metabolism might be inconsequential to the production of secondary metabolites themselves. Altogether our results caution against overt reliance on transcriptome and translatome data as a proxy to phenotypic expression of actinobacterial BGCs 13,62,63 .…”
Section: Discussionmentioning
confidence: 60%
“…Several translationally controlled genes reported here can be considered part of a common stress response; an endonuclease, a protease, and thioredoxin M all exhibited increases in protein synthesis without a corresponding increase in mRNA. Translational control of these genes may be a faster way of coordinating their expression than a transcription program (15,22). It is not known whether these genes have a common effector; C i depletion induces many ncRNAs with unknown targets (34).…”
Section: Discussionmentioning
confidence: 99%
“…For example, antibiotic biosynthesis pathways in Streptomyces coelicolor were found to be "translationally induced" as cells enter stationary phase, as evidenced by increases in translational efficiency for genes in secondary metabolism (14). Also working with Streptomyces coelicolor, Bucca et al reported an increase in translational efficiency of several genes upon temperature shift from 30°C to 42°C (15). Ribosome profiling of Synechocystis during C i depletion might, thus, reveal new mechanisms for how carbon limitation is ultimately transduced to an altered proteome.…”
mentioning
confidence: 99%
“…Several proteins containing CSD show varied nucleic acid-binding activities that affect gene transcription, DNA replication, and DNA repair, while others interact with mRNA to affect translational efficiency 12 , 13 , 23 , 24 . Recently, the cold shock proteins have been highlighted the likely importance in adaptation to stress that were not previously considered to be part of the heat-shock stimulon in Streptomyces coelicolor 25 . Thus, we hypothesized that proteins containing CSD from thermophilic bacteria, which already show adaptability to high temperatures, might serve as updated stress-response elements to improve high temperature tolerance of other microbes.…”
Section: Introductionmentioning
confidence: 99%